Multimodal biometric systems : security and applications - Gupta, Rashmi; Khari, Manju (Boca Raton, FL : CRC Press, 2022)
"Several governments around the world are calling for the use of biometric systems to be used to deliver crucial societal functions, therefore making it an urgent need to act. The current performance of some biometric systems regarding the combination of error rate, robustness, and system security may prove to be inadequate for large-scale applications to process millions of users at a high throughput rate. This book focuses on fusion in biometric systems. It discusses the present level, the limitations, and proposed methods to improve performance. It describes the fundamental concepts, current research, and security related issues. The book will present a computational perspective, identify challenges, and cover new problem-solving strategies, offering solved problems and case studies to help with reader comprehension and deep understanding. This book is written for researchers, practitioners, both graduate and post graduate students, and those working in various engineering fields such as Systems Engineering, Computer Science, Information Technology, Electronics, and communications"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Biometric identification; COMPUTERS / Security / General